Effects of thermal insulation on thermal comfort in low-income tropical housing. (October 2017) - Hashemi, Arman
Abstract: This paper evaluates the effects of thermal insulation on thermal comfort in low-income tropical housing in Uganda. Dynamic thermal simulations are conducted to assess the effects of wall, roof and floor insulation strategies. 96 combination scenarios are simulated for various geometries, insulation and construction methods. Adaptive approach is used to evaluate the conditions within the case study buildings. The results indicate that external wall insulation improves thermal comfort in all conditions whereas internal wall and floor insulation may deteriorate the conditions. Roof insulation is the most effective strategy to reduce the risk of overheating. Due to the effectiveness of roof insulation and marginal improvements of external wall insulation, especially for brick walls, wall insulation may be disregarded when used in conjunction with roof insulation.